Resilience in supply networks: Definition, dimensions, and levels. (2017) - Reyes Levalle, Rodrigo; Nof, Shimon Y.
Abstract: Oftentimes, seemingly robust systems fail, almost inexplicably, due to unforeseen events leading to disruption. Exploration and research of the mechanisms behind the failure of such systems have revealed that those capable of surviving are not robust, but resilient. This has spawned a stream of research on the resilience of different complex systems, from ecosystems, to the human body, to supply chains and communication networks. Supply networks are complex adaptive systems in which a subset of agents create flow and are required to deliver such flow to sink agents located at the other end of the network. Delivery of flow under pre-defined service conditions requires resilient design and operation protocols. In this article, a supply network formalism is introduced, and the concept and dimensions of resilience in supply networks, explored. Five core components of resilience are derived from reviewed definitions; two resilience dimensions, structure and control protocols, and two resilience levels, agent and network level, are characterized based on insights from articles in literature. Finally, emerging trends in resilience research as well as current research gaps are presented and future work directions outlined.